An overview on the effect of heat-treatment and cooling rates on Ni-based superalloys. (2021) - Sahu, Saroj Kumar; Mishra, Dinesh Kumar; Behera, Ajit; Dalai, Renu Prava
Abstract: Ni-based superalloys are applicable in the gas-turbine engine components and aerospace industries because they maintain their mechanical properties and tribological properties at high temperatures. Alloying with Al, Ti, Nb, and Fe, it forms the γ' and γ'' precipitates. The volume fraction and morphology of the γ' precipitates affect the mechanical properties and also they can change their morphology with heat treatment temperature, time, and cooling rates. Commonly use two-step heat treatment process for Ni-based super-alloys is heating up to 1010 °C for 2 hrs plus heating up to 788 °C for 8 hrs. By increasing the average size of the γ' precipitates, yield strength increases, but ductility reduces. Further, the γ' phase can precipitate coherently with the γ phase and enhance the mechanical properties. Hence in the present review focuses on the consequences of heat treatment temperature and cooling rates on the Ni-based super-alloys to efficiently optimize their performance and durability.